Development of the Rumah Karya application in the educational technology study program as a media database for the works of lecturers and students - Sella Mawarni; Hartoto Hartoto (Universitas Negeri Yogyakarta, 2023)
This research aims to produce Rumah Karya applications that provide a media product database for lecturers and students in the Educational Technology Study Program at Makassar State University. The research method used in this research is RD (Research and Development), with the ADDIE development model divided into five stages: analysis, design, development, implementation, and evaluation. The Rumah Karya application has been validated by the head of a study program as a material expert and an information technology (IT) expert. Validation from material experts obtained an average of 98% very feasible category, and validation from IT experts obtained an average of 92% very feasible category. This application has been tested by lecturers and students in the Educational Technology study program, which produces an average of 83.8% which includes a very feasible category. The Rumah Karya application has been registered as intellectual property rights at Makassar State University. The Rumah Karya application has been implemented and integrated with the Educational Technology study program website. This research has the potential to carry out further research related to additional development features in Rumah Karya that can enhance the user experience in using the application. This research can also be extended to other study programs or other educational institutions to measure the generalization of Rumah Karya's application in improving the quality of media products in educational institutions.